Studies on The Functionality of the Hong Kong's Footpath System - Fan, Chuxi (Transactions on Engineering and Technology Research, 2024)
As the core pedestrian space in the city, the footpath is related to the walking experience and travel choices, affects the transportation system, promotes commercial, social, and cultural activities, and is a key carrier of urban vitality and safety. Hong Kong's footpath system is known for its multi-layered and three-dimensional structure, which effectively connects urban spaces through a complex network. However, Hong Kong still has problems such as insufficient ground crossing facilities and chaotic design and management. Future trends show that footpath design will pay more attention to pedestrian experience and needs, emphasizing functional diversity and refined services. The existing Hong Kong footpath strategy focuses on convenience, vitality, and diversity, while the design strategy emphasizes environmental, cultural integration, and sustainability. To meet the changing needs of people for footpath activities, it is necessary to strengthen guidance, greening, and cultural integration. By exploring the design of Hong Kong footpaths, this paper aims to provide a reference for a more comprehensive and systematic solution to the problems faced by the footpath system, thereby improving the quality of life of citizens and the overall livability of the city.